6A13-T6 high-strength aluminium alloy beams: Test, finite element analysis and design recommendations. Issue 8 (June 2023) - Zhong, Chang-jun; Chen, Gang; Feng, Ruo-qiang; Huang, Yong-qi
6A13-T6 high-strength aluminium alloy material has excellent mechanical properties, but the lack of research on its mechanical properties is the biggest obstacle to its application in building engineering. This paper reports the test results of material tensile and member bending and finite element simulation to reveal the constitutive curve, failure mode, and ultimate bearing capacity of 6A13-T6 high-strength aluminium alloy. Specifically, the non-proportional yield strength of 6A13-T6 exceeds 340 MPa, the ultimate strength reaches 352 MPa, and the elongation after fracture is 14.5%. All the tested members have an evident bending phenomenon, and the width-to-thickness ratio determines the significant degree of local buckling. The Chinese code takes too much account of the reduction of section thickness and does not consider the plastic development of the section, so the predicted bearing capacity is conservative. The American code does not fully consider the effect of section plasticity, which is also conservative. The finite element modelling technology adopted is reasonable and feasible. The section can provide a greater bearing capacity when it enters the plastic strengthening stage. The local buckling will limit the bearing capacity, while the plate group effect can improve the bearing capacity of the member. It is suggested to increase the section plastic development coefficient in the Chinese code to 1.15. The results of this survey provide a reference for designers and engineers to use 6A13-T6 conveniently.